2007
DOI: 10.1086/511807
|View full text |Cite
|
Sign up to set email alerts
|

The Rotation Velocity Attributable to Dark Matter at Intermediate Radii in Disk Galaxies

Abstract: We examine the amplitude of the rotation velocity that can be attributed to the dark matter halos of disk galaxies, focusing on well measured intermediate radii. The data for 60 galaxies spanning a large range of mass and Hubble types, taken together, are consistent with a dark halo velocity log V h = C + B log r with C = 1.47 +0.15 −0.19 and B ≈ 1 2 over the range 1 < r < 74 kpc. The range in C stems from different choices of the stellar mass estimator, from minimum to maximum disk. For all plausible choices … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
136
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 144 publications
(203 reference statements)
14
136
3
1
Order By: Relevance
“…This implies a dark matter halo consistent with the near-universal halo found by McGaugh et al (2007) and Walker et al (2010). Unfortunately, this empirical dark matter halo is not consistent with ΛCDM (McGaugh et al 2007), though presumably it can be accommodated by invoking feedback or some other mechanism.…”
Section: Ret II Hor I and Hyd Iimentioning
confidence: 71%
See 2 more Smart Citations
“…This implies a dark matter halo consistent with the near-universal halo found by McGaugh et al (2007) and Walker et al (2010). Unfortunately, this empirical dark matter halo is not consistent with ΛCDM (McGaugh et al 2007), though presumably it can be accommodated by invoking feedback or some other mechanism.…”
Section: Ret II Hor I and Hyd Iimentioning
confidence: 71%
“…This is done with the scaling relations of McGaugh et al (2007) and Walker et al (2009), the results of which are tabulated in Table 5. Walker et al (2010) showed that the distinct relations of McGaugh et al (2007) and Walker σ Newton : Predicted velocity dispersion assuming M/L = 2 and that the objects are dark-matter-free.…”
Section: Scaling Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been conclusively demonstrated that spiral galaxy rotation curves are well recovered in MOND purely by the baryon distribution without any parameter adjustments (Sanders & McGaugh 2002;McGaugh 2004McGaugh , 2005aSanders & Noordermeer 2007), and MOG is reported to also do well on this account (Brownstein & Moffat 2006). In contrast, the DM approach can only poorly reproduce the vast variety of rotation curves, and cannot explain the amazing regularities found in them (McGaugh 2004;McGaugh et al 2007;Gentile et al 2009;Milgrom 2009a). Notably, the realisation (Gentile et al 2009;Milgrom 2009a) that the ratio of DM mass to baryonic mass within the DM core radius is constant despite the large variation in the DMto-baryonic-matter ratio globally within galaxies cannot be understood within the DM hypothesis.…”
Section: Non-newtonian Weak-field Gravitymentioning
confidence: 99%
“…The Cuspy Halo Problem refers to the discrepancy between the galactic dark matter halo density profiles predicted by ΛCDM galaxy formation simulations and the density profiles inferred from galactic rotation curves [29,30]. Galaxies are believed to form through a process of hierarchical clustering [31], in which large galaxies are formed via mergers of many smaller objects, with the initial density fluctuations arising during the Big Bang.…”
Section: The Cuspy Halo Problemmentioning
confidence: 99%